Feature selection and ensemble methods for bioinformatics : Algorithmic classification and implementations - Okun, Oleg. (Hershey PA : Medical Information Science Reference, 2011)
"This book offers a unique perspective on machine learning aspects of microarray gene expression based cancer classification, combining computer science, and biology"--Provided by publisher.
Keywords: Bioinformatics; Bioinformatics